What are the Empirical Determinants of International Tourist Arrivals and Expenditures? An Empirical Application to the Case of Sao Tome and Principe - Montes-Rojas, Gabriel; Barroso, Rafael (World Bank, Washington, DC, 2020)
The link between tourism and growth is very important for some countries, especially small island countries like São Tomé and Príncipe. This paper investigates the empirical determinants of tourism outcomes (tourist arrivals and expenditures) and uses the findings to assess the performance of the tourism sector in São Tomé and Príncipe. The paper confirms most of the results found in the literature on the general determinants of tourism. Tourist arrivals increase with the gross domestic product and exports of the host country, as well as with increased air connectivity. Real exchange rate variations affect tourist decisions, and tourism outcomes have a persistent effect. The paper also finds that a positive attitude toward acceptance of lesbian, gay, bisexual, and transgender people increases tourist arrivals. Unfortunately, the relationship between digital presence and tourism outcomes could not be tested. The paper shows that São Tomé and Príncipe can do better in tourist arrivals, but it already has good performance on expenditures per tourist. Improving air connectivity is key to attracting more tourists, and demand for tourism is not very price sensitive, implying that the strategy to focus on high-spending tourists is the correct one.